Concentration and Quantification of SARS-CoV-2 RNA in Wastewater Using Polyethylene Glycol-Based Concentration and qRT-PCR - Farkas, Kata; Hillary, Luke S.; Thorpe, Jamie; Walker, David I.; Lowther, James A.; McDonald, James E.; Malham, Shelagh K.; Jones, Davey L. (Methods and protocols, 2021)
Wastewater-based epidemiology has become an important tool for the surveillance of SARS-CoV-2 outbreaks. However, the detection of viruses in sewage is challenging and to date there is no standard method available which has been validated for the sensitive detection of SARS-CoV-2. In this paper, we describe a simple concentration method based on polyethylene glycol (PEG) precipitation, followed by RNA extraction and a one-step quantitative reverse transcription PCR (qRT-PCR) for viral detection in wastewater. PEG-based concentration of viruses is a simple procedure which is not limited by the availability of expensive equipment and has reduced risk of disruption to consumable supply chains. The concentration and RNA extraction steps enable 900–1500× concentration of wastewater samples and sufficiently eliminates the majority of organic matter, which could inhibit the subsequent qRT-PCR assay. Due to the high variation in the physico-chemical properties of wastewater samples, we recommend the use of process control viruses to determine the efficiency of each step. This procedure enables the concentration and the extraction the DNA/RNA of different viruses and hence can be used for the surveillance of different viral targets for the comprehensive assessment of viral diseases in a community.